THE INFLUENCE OF SOLAR RADIATION ON RADIO SIGNAL AT UHF BAND - Roslan, Umar; M. S., Marhamah; N., Hazmin (2018)
One of the common threats to earth-space communication is the data losss, which is possibly caused by weather factors. In this paper, the effect of solar radiation on radio signal at ultra-high frequency (UHF) band is investigated. The average radio frequencies found at UHF band were 382.5 MHz, 945.0 MHz, 1800.0 MHz, 1867.5 MHz and 2137.5 MHz. The variation of all prominent peaks begins during sunrise and sunset, where all most of the prominent peaks show weak signal strength during the daytime compared during the night time. We can conclude that the radio signals were depending on the presence of solar radiation and the level of solar radiation measured during daytime and night time as solar radiation measured differently as 376.0246 W/m 2 and 428.9846 W/m 2 during 26 th July and 27 th July respectively.